An Empirical Study on Impact of Demographic Factors on Determining Training Needs of Supervisors - Chinnadurai, P.; Arul, P. G. (Prabandhan: Indian Journal of Management, 2011)
Supervisors are the most important assets of an organization. They play a decisive role in obtaining quality work from their subordinates, and they are treated as a dynamic element for giving life to an organization. The success and growth of an organization depend largely upon the caliber and performance of its supervisors. Therefore, every organization must take an effort to improve the quality of its supervisors for which the organization should design a supervisory training programme. Every training programme must be related to the specific needs of the individual employees; likewise, the supervisory training programmes also should be linked to the specific needs of the supervisors. A training programme should be conducted only after the training needs are analyzed specifically and clearly. The effectiveness of a supervisory training programme can be judged only with the help of the training needs of the supervisors identified in advance. The supervisory training programmes which are ill directed and are inadequately focused do not serve the purpose of the trainers, the trainees, or the organization, hence, identification of supervisory training needs based on supervisors' demographic factors, becomes the top priority of every progressive organization. In this context, the authors have made an attempt to identify the training needs of supervisors for interpersonal skills development and the paper also aims to examine the influence of certain demographic factors on the training needs of Supervisors towards interpersonal skills development. The research study was conducted in a power generating, profit making public sector organization situated in the northern part of Tamil Nadu, South India. The results of the research have been discussed in this article.